SISTEM MONITORING JARINGAN REALTIME BERBASIS INTERNET CONTROL MESSAGE PROTOCOL - Muhammad Faisal Qomarudin; Agit Amrullah (JINTECH: Journal Of Information Technology, 2022)
Network monitoring in the company is more extensive and complex, each device must be connected to the network so that there are no obstacles when there is receiving and sending data from various devices. Problems on computer networks cannot be predicted when they occur and continuous monitoring is needed to ensure the network is connected properly and it is difficult to troubleshoot network damage. Therefore, a network monitoring system is needed to check the network so that administrators can find out network conditions. By using the Internet Control Message Protocol to check the network continuously so that it can find out the condition of the device, taking into account the latency and data obtained by Packet Internet Gopher. Network checks and notifications use a backdoor working system or through a background process, control the process is also a network check log to find out which devices are often disconnected and to make network troubleshooting easier. In this paper, will be building a network monitoring system that displays network status and monitors the network continuously with telegram notifications, network logs to facilitate troubleshooting, Internet Protocol management and backdoor system settings by the name of SIMONIT.